Anti-rebel - Mahinay, Mikey Ashlie Laconico (2012)
"Anti-Rebel explores the point of view of the middle-class that are left out of the institutionalized system activism in the University of the Philippines. The film relies on Social Construction of Reality to explain why people accept things because "of the way it is". An attempt to enter and make sense of the system by an outsider is presented in this film."